1993
DOI: 10.1073/pnas.90.16.7632
|View full text |Cite
|
Sign up to set email alerts
|

Tat protein of human immunodeficiency virus type 1 represses expression of manganese superoxide dismutase in HeLa cells.

Abstract: Using a HeLa cell line stably transfected with the tat gene from human immunodeficiency virus type 1, we have found that the expression of the regulatory Tat protein suppresses the expression ofcellular Mn-containing superoxide dismutase (Mn-SOD). This enzyme is one of the cell's primary defenses against oxygen-derived free radicals and is vital for maintaining a healthy balance between oxidants and antioxidants. The parental HeLa cells expressed nearly equivalent amounts of Cu,Zn-and Mn-SOD isozymes. Those ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
2
2

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(141 citation statements)
references
References 54 publications
6
131
2
2
Order By: Relevance
“…A 10 -40% decrease in GSH content can completely inhibit lymphocyte activation in vitro (8). Indeed, the very fact that Tat modulates GSH biosynthesis in addition to suppressing the activity of manganese superoxide dismutase (27,41,42) may testify to the importance of redox regulation in HIV pathogenesis. Specifically, these prooxidative effects of Tat may enhance its NF-B-dependent transactivating potential (6,7,42,43), suggesting that the effect of Tat on the GSH status is a specific and self-promoting event in HIV pathology.…”
Section: Fig 3 Gcs-ls Protein Content Is Decreased In Liver and Erymentioning
confidence: 99%
See 1 more Smart Citation
“…A 10 -40% decrease in GSH content can completely inhibit lymphocyte activation in vitro (8). Indeed, the very fact that Tat modulates GSH biosynthesis in addition to suppressing the activity of manganese superoxide dismutase (27,41,42) may testify to the importance of redox regulation in HIV pathogenesis. Specifically, these prooxidative effects of Tat may enhance its NF-B-dependent transactivating potential (6,7,42,43), suggesting that the effect of Tat on the GSH status is a specific and self-promoting event in HIV pathology.…”
Section: Fig 3 Gcs-ls Protein Content Is Decreased In Liver and Erymentioning
confidence: 99%
“…Tat is associated with AIDS-related dementia (38) as well as two of the most frequent cancers associated with AIDS: Kaposi's sarcoma (39) and B cell lymphoma (40). Tat has been shown to lower total and reduced GSH concentration in vitro in various cell lines and also the total sulfhydryl content in vivo in a transgenic animal model (27,41,42). In addition, Tat is sufficient to cause both the enhanced activation of NF-B and the increased susceptibility to apoptosis, observed with HIV (42)(43)(44).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…It has been reported that HIV-1 Tat by itself does not activate NF-B, but rather potentiates the TNF-␣-mediated activation of NF-B (Westendorp et al, 1995). This potentiation was due to a change in the redox state of the cells caused by down-regulation of magnesium superoxide dismutase (Mn-SOD) expression (Flores et al, 1993;Westendorp et al, 1995). In contrast to Tat, gp120 is unable to inhibit activity and expression of Mn-SOD, but it can amplify TNF-␣-induced NF-B-binding activity in CD4-positive Jurkat T cells (Shatrov et al, 1996).…”
mentioning
confidence: 99%
“…Microglia exposed to Tat induce nitric-oxide synthase and NO production, and this induction is also dependent upon NF-B (26). On the other hand, negative effects include repression of major histocompatibility class-I gene promoter activity (27) and of the important antioxidant enzyme maganese-superoxide dismutase (28). Interestingly, a deregulation of cytokine expression and/or secretion is a hallmark of HIV infection (29 -32).…”
mentioning
confidence: 99%